1999
DOI: 10.1021/jf981265o
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Value of Mediterranean Sheep's Burnet (Sanguisorba minorSsp.muricata)

Abstract: A survey of compositional characteristics of the aerial part of sheep's burnet (Sanguisorba minor ssp. muricata) growing in Mediterranean French pastures has been undertaken. Investigations with scanning electron microscopy gave the morphological structure of this plant, in particular for akene ornamentation. Taxonomic characters confirmed the identification of the muricata subspecies. Moisture, ash, free sugars, cellulose, amino acids, and fatty acids of the whole aerial part were determined. Besides the majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 10 publications
0
9
1
1
Order By: Relevance
“…Similar to our study, Elgersma et al 29 suggested that α-linolenic acid was the main fatty acid (46.96%) in S. minor forage, while linoleic and palmitic acids were found in smaller amounts (21.24% and 15.83%, respectively). In contrast, Viano et al 30 who studied the nutritional value of S. minor spp. muricata also detected palmitic, linoleic and α-linolenic Small Latin letters in the same row indicate significant differences between means of the same plant part (leaves + stems, and roots) according to the Tukey's HSD test (P < 0.05).…”
Section: Chemical Compositionmentioning
confidence: 96%
“…Similar to our study, Elgersma et al 29 suggested that α-linolenic acid was the main fatty acid (46.96%) in S. minor forage, while linoleic and palmitic acids were found in smaller amounts (21.24% and 15.83%, respectively). In contrast, Viano et al 30 who studied the nutritional value of S. minor spp. muricata also detected palmitic, linoleic and α-linolenic Small Latin letters in the same row indicate significant differences between means of the same plant part (leaves + stems, and roots) according to the Tukey's HSD test (P < 0.05).…”
Section: Chemical Compositionmentioning
confidence: 96%
“…Anecdotal evidence suggests that small burnet is highly palatable to both livestock and wildlife; however, the actual preference of small burnet relative to other forages has not been quantified, and the forage quality of small burnet has not been adequately described (Arzani et al, 2006; Duru, 1997; Kendir, 1999; Viano et al, 1999). Future evaluations of small burnet should characterize forage quality and palatability in comparison with well‐known forages such as alfalfa.…”
Section: Discussionmentioning
confidence: 99%
“…Kendir (1999) characterized the variation among native populations of small burnet collected from the Ankara rangelands (Turkey) and the cultivar Bünyan 80. Viano et al (1999) characterized small burnet for nutritional value, which included mineral, amino acid, fatty acid, and protein content but provided no information on digestibility or relative reference to a more common forage. Duru (1997) also mentions small burnet as a component of a meadow plant community tested for forage quality.…”
mentioning
confidence: 99%
“…Kurağa dayanıklı bitkilerin bu strese adaptasyonunu sağlamak sorunun çözümüne uygun bir yaklaşım olabilir (Gür ve Şan, 2017). Kuraklık stresine dayanıklı bitki türlerinin belirlenmesi, tolerans mekanizmalarının açığa çıkarılması, kurağa dayanıklı bitki genetik kaynaklarının korunması ve aktarımına yönelik girişimler, kuraklığın yol açtığı zararları azaltmada etkin rol oynayabilir (Yıldırım ve Kodal, 1998).…”
Section: Introductionunclassified